Cultural, autobiographical and absent memories of orphanhood : the girls of Nazareth House remember - Edwards, Delyth (Palgrave Macmillan, 2020)
This book offers an empirically informed understanding of how cultural, autobiographical and absent memories of orphanhood interact and interconnect or come into being in the re-telling of a life story and construction of an identity. The volume investigates how care experienced identities are embedded within personal, social and cultural practices of remembering. The book stems from research carried out into the life (hi)stories of twelve undervalued 'historical witnesses' (Roberts, 2002) of orphanhood: women who grew up in Nazareth House children's home in Belfast, Northern Ireland, during the 1940s, 50s and 60s. Several themes are covered, including histories of care in Northern Ireland, narratives and memories, sociologies of home, and self and identity. The result is an impressive text that works to introduce readers to the complexity of memory for care experienced people and what this means for their life story and identity.